(untitled) (Edad Media. Revista de Historia, 2026)
This study analyzes the structure and composition of the female household at the court of Navarre during the reign of Queen Blanche and shortly after (1421-1451). Relying on a prosopographical approach, the author traces the careers of ladies-in-waiting , maidens, and female servants associated within royal lodgings. Special emphasis is placed on their active role in the Queen’s Chamber, in the upbringing of the royal children (infantes), and in households management. Family networks, strategic marriages, and long-standing service within the households of the Princess of Viana and the Infanta Leonor are closely examined in order to underscore the social and political relevance of these women in a late-medieval courtly environment.